Anatomoclinical study of 30 cases of sclerosing sweat duct carcinomas (microcystic adnexal carcinoma, syringomatous carcinoma and squamoid eccrine ductal carcinoma). (15th April 2015) - Frouin, E.; Vignon‐Pennamen, M.D.; Balme, B.; Cavelier‐Balloy, B.; Zimmermann, U.; Ortonne, N.; Carlotti, A.; Pinquier, L.; André, J.; Cribier, B.
Abstract Background Microcystic adnexal carcinoma (MAC), syringomatous carcinoma (SC) and "Squamoid eccrine ductal carcinoma" (SEDC) are rare sclerosing adnexal tumours. Objective To understand the histogenesis of these tumours and possible clinical implications. Methods We conducted a retrospective study of 30 cases, 18 MAC, 5 SC and 7 SEDC reviewed and classified by a panel of dermatopathology experts, with immunohistochemical analysis of keratins, including K77, a new keratin specific of eccrine ducts, and PHLDA1 expressed in adnexal structures. Results There was a strong female predominance, with only five cases occurring in men. Patients with MAC and SC were younger (mean age 56 and 47 years) than those with SEDC (mean age 81 years). The most common localization was the cheek in SC and SEDC and the periocular area in MAC. Two cases of SEDC were found in organ transplant patients. No recurrence or metastases were observed after complete surgery of MAC, or SC (mean follow‐up 7.2 years and 4.7 years), whereas one case of SEDC recurred and another could not be fully excised. MAC and SC had similar histological features, except for cysts. In MAC, calcifications, granulomas, connection to follicles, keratin expression pattern, PHLDA1 positivity and K77 negativity indicated a follicular histogenesis, whereas in SC, K77 positivity and keratin expression pattern were consistent with a differentiation towards eccrine apparatus. SEDC was composed of strands centred by ducts and nests with squamous differentiation and displayed K77 ductal positivity in all cases, a finding consistent with an eccrine origin. Conclusion Our study demonstrated that MAC and SC have similar clinical characteristics, although histogenesis differs and show arguments for the individualization of SEDC.